1993
DOI: 10.1203/00006450-199312000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Hypoxemia Enhances and Acute Hypoxemia Attenuates Laryngeal Reflex Apnea in Young Lambs

Abstract: ABSTRACT. To determine the influence of an altered carotid body function on the laryngeal chemoreflex (LCR) response, reflex apnea was induced by laryngeal water stimulation during normoxia or acute hypoxia in unanesthetized awake lambs in which the ventilatory response to acute hypoxia was attenuated by prolonged postnatal hypoxemia. Prolonged hypoxemia (H) was induced in seven lambs for 12 d after birth through exposure to 0.10 fraction of inspired oxygen. Five control lambs were kept in 0.21 fraction of ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Although not apparent in the C group in this study, it has previously been shown that the magnitude of cardiorespiratory inhibition in response to LCR stimulation is strongest in the newborn period and decreases thereafter (8,9,33). Both these factors would imply that the most marked effects of nicotine are to be seen early.…”
Section: Nicotine Impairs Autoresuscitation In Lambsmentioning
confidence: 61%
See 3 more Smart Citations
“…Although not apparent in the C group in this study, it has previously been shown that the magnitude of cardiorespiratory inhibition in response to LCR stimulation is strongest in the newborn period and decreases thereafter (8,9,33). Both these factors would imply that the most marked effects of nicotine are to be seen early.…”
Section: Nicotine Impairs Autoresuscitation In Lambsmentioning
confidence: 61%
“…Sladek et al (8), Grogaard et al (9), and Grogaard and Sundell (13) could demonstrate that surgical denervation of the CB chemoreceptors resulted in extreme prolongation of LCR-induced apnea, whereas stimulation of CB chemoreceptors by hypoxemia or ␤-adrenergic agonists shortened LCR-induced apnea and the postapneic respiratory depression. We therefore compared the LCR response in room air with the response during CB chemoreceptor stimulation with mild hypoxia.…”
Section: Cb Chemoreceptor Activity and Lcr Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Here, too, the results with respect to hypoxia are complex: the duration of apnea with intralaryngeal water instillation has generally been shortened by acute hypoxia (Sladek et al,1993; Milerad and Sundell, 1999; Sundell et al, 2003), although not significantly at all ages. As pointed out by Milerad and Sundell (1999), the apneic response to laryngeal stimulation during acute hypoxia may be attenuated by carotid chemoreceptor mediated ventilatory drive, but enhanced by the attendant hypocapnia.…”
Section: Discussionmentioning
confidence: 97%